Python for DevOps Master Class 2022 : CI/CD, Github Actions, containers and microservices. (Pragmatic AI Solutions, 2022)
Learn to master DevOps with the Python Language 00:00 Intro 02:12 What is DevOps? 05:00 Create Github Repo 18:00 Statements in Python using Colab 30:32 Create Python Scaffold using Github Codespaces 37:00 Create Python Virtualenv and add to ~/.bashrc 40:53 Launch AWS CloudShell and checkout code 42:09 Launch AWS Cloud9 46:00 Freezing packages with pip freeze 55:00 Setup Github Actions 01:14:31 Test code with Github Actions and Pytest 01:23:00 Build CLI with Python and Python Fire 01:25:52 Build Python Lambda Functions 01:40:00 Build AWS Step Functions 01:43:00 Build Python Fire Step Functions 01:57:00 Build Containerized Microservice with FastAPI and AWS App Runner.